The anal pore route is efficient to infect Amblyomma spp. ticks with Rickettsia rickettsii and allows the assessment of the role played by infection control targets - Nassar, Marcelly Bastos; Pavanelo, Daniel B.; Labruna, Marcelo B.; Daffre, Sirlei; Esteves, Eliane; Fogaça, Andréa C. (Frontiers in Cellular and Infection Microbiology, 2023)
Adult Amblyomma sculptum and Amblyomma aureolatum ticks are partially refractory to Rickettsia rickettsii when fed on infected hosts, hindering the functional characterization of potentially protective targets in the bacterial acquisition. In the current study, we used the anal pore route to infect adult A. sculptum and A. aureolatum ticks with R. rickettsii and to assess the effects of the knockdown of microplusin in infection control. The anal pore route was efficient to infect both species, resulting in a prevalence of around 100% of infected ticks. Higher loads of R. rickettsii were detected in microplusin-silenced A. aureolatum in relation to the control, as previously obtained when microplusin-silenced ticks were fed on R. rickettsii-infected rabbits. This is the first report showing R. rickettsii infection through the anal pore in Amblyomma ticks, highlighting this route as a powerful tool to assess the role played by additional targets in the control of pathogens.